2013
DOI: 10.5430/afr.v2n3p45
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal and Cross-Industry Study on the Stability of Financial Ratios of Malaysian Companies

Abstract: The purpose of this study is to test whether a set of six financial ratios that have been used extensively by practitioners and researchers and found to be useful for various purposes including company financial performance evaluations are stable across three different industry sectors and whether they are stable over time. The sample comprises a total of 180 listed companies covering a period of five years from 2006 to 2010. Analysis of variance and post hoc multiple comparisons were carried out for each rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…A study of Malaysian companies (Yap, Zulkifflee, & Chong, 2013) revealed similar results. The results of that study were that EBITTA, CCL, TDTA and TDSF varied across some industries but did not vary over time and there were no significant interaction effects between Time and Sector.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…A study of Malaysian companies (Yap, Zulkifflee, & Chong, 2013) revealed similar results. The results of that study were that EBITTA, CCL, TDTA and TDSF varied across some industries but did not vary over time and there were no significant interaction effects between Time and Sector.…”
Section: Discussionmentioning
confidence: 62%
“…The ratios that were selected for the study are ratios which have been used and identified as effective in several past studies (Yap, Zulkifflee, & Chong, 2013). The ratios are presented in Table 2 below.…”
Section: Financial Ratiosmentioning
confidence: 99%